Translating SARS-CoV-2 wastewater-based epidemiology for prioritizing mass vaccination: a strategic overview - Dharmadhikari, Tanmay; Yadav, Rakeshkumar; Dastager, Syed; Dharne, Mahesh (Environmental Science and Pollution Research, 2021)
The inception of the novel coronavirus has forced the world into despair. Rapid progress has been made in addressing the situation, and various clinical diagnostic methods were developed for early detection of transmission. However, with a rapidly increasing number of infected populations worldwide, the testing of each individual was impractical. The wastewater-based epidemiology (WBE) has been implemented to evaluate disease outbreaks as an early warning system for pandemic preparedness. Numerous studies reported the presence of SARS-CoV-2 in the open drains and STPs across the globe via recovery efficiency of surrogate virus from existing virus concentration protocols. However, the such reported studies did not justify the use of WBE to identify or pinpoint the specific hotspots of transmission which could be prioritized for rapid efforts to contain or accelerate active vaccination efforts. Identifying precise locations of hotspots could be an essential aspect in controlling the outbreak and surge of wave by prioritizing the region for primary outbreak response. This article focuses on the issues relating to the primary focus for WBE that can be adapted, and its suitability for utilization in the mass vaccination program is discussed. Effective use of WBE information in terms of source tracking might be crucial as we move towards mass vaccination to control outbreaks of COVID-19 pandemic.
Keywords: Epidemiology; Policy making; SARS-CoV-2; Vaccination; wastewater

High throughput sequencing based direct detection of SARS-CoV-2 fragments in wastewater of Pune, West India - Dharmadhikari, Tanmay; Rajput, Vinay; Yadav, Rakeshkumar; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Kamble, Sanjay P.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2022)
Given a large number of SARS-CoV-2 infected individuals, clinical detection has proved challenging. The wastewater-based epidemiological paradigm would cover the clinically escaped asymptomatic individuals owing to the faecal shedding of the virus. We hypothesised using wastewater as a valuable resource for analysing SARS-CoV-2 mutations circulating in the wastewater of Pune region (Maharashtra; India), one of the most affected during the covid-19 pandemic. We conducted study in open wastewater drains from December 2020- March 2021 to assess the presence of SARS-CoV-2 nucleic acid and further detect mutations using ARTIC protocol of MinION sequencing. The analysis revealed 108 mutations across six samples categorised into 39 types of mutations. We report the occurrence of mutations associated with Delta variant lineage in March-2021 samples, simultaneously also reported as a Variant of Concern (VoC) responsible for the rapid increase in infections. The study also revealed four mutations; S:N801, S:C480R, NSP14:C279F and NSP3:L550del not currently reported from wastewater or clinical data in India but reported worldwide. Further, a novel mutation NSP13:G206F mapping to NSP13 region was observed from wastewater. Notably, S:P1140del mutation was detected in December 2020 samples while it was reported in February 2021 from clinical data, indicating the instrumentality of wastewater data in early detection. This is the first study in India to demonstrate utility of sequencing in wastewater based epidemiology to identify mutations associated with SARS-CoV-2 virus fragments from wastewater as an early warning indicator system. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: ARTIC protocol; Epidemiology; Metagenomics; Nanopore sequencing; SARS-CoV-2; wastewater